A provocation to mission: Constance Padwick's study of Muslim devotion - Laing, Catriona (Islam and Christian-Muslim relations, 2013)
This article offers an examination of the work of Constance Padwick (1886-1968), who served as a ‘literature missionary’ with the Church Missionary Society and the International Missionary Council in Egypt and Palestine in the first half of the twentieth century. Through a study of Padwick's life-long engagement with popular Muslim devotional prayers, the article demonstrates how she was inspired to use language, devotion and liturgy to call for a richer, bolder and deeper Christian presence in the Muslim world. Formed by the prevailing Evangelical tradition of the epoch, Padwick was drawn to Islam's mystical tradition. Her commitment to teasing out underlying similarities between the two traditions influenced the theology of mission that she developed, as her study of Muslim devotions led her to encourage a greater emphasis on the contribution that Arabic Christian devotional literature could make to Protestant missions in the Muslim world. In addition to shaping a specific missiological approach, the experience of Islamic popular piety led her to exhort her colleagues to cooperate more closely with the Eastern churches in order to build up and strengthen the ancient Christian presence in the Arab world.